2020
DOI: 10.14203/metalurgi.v35i3.558
|View full text |Cite
|
Sign up to set email alerts
|

Pelindian Zirkonium Dari Tailing Magnetik Pasir Zirkon Hasil Roasting Menggunakan Naoh

Abstract: Tailing pertambangan adalah penyebab sebagian besar pencemaran lingkungan yang terkait dengan industri ekstraktif. Peningkatan risiko pencemaran lingkungan telah diamati di seluruh dunia karena sejumlah besar pengolahan bijih kadar rendah. Dalam penelitian ini, pemulihan zirkonium dari tailing magnetik pasir zirkon telah diselidiki. Tujuan dari studi ini adalah untuk mengetahui pengaruh kondisi operasi pencucian terhadap pemulihan zirkonium dari tailing magnetik pasir zirkon. Tailing magnetik pasir zirkon yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, several studies have recently revealed that zircon waste contains valuable minerals that can be reused for various purposes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have recently revealed that zircon waste contains valuable minerals that can be reused for various purposes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This is because these minerals contain the iron (Fe) element, which is considered to be used as a precursor for the Fe3O4 synthesis, which in this research will be composited with MIL-100(Fe). Utilizing secondary sources of zircon mining waste is one effort to maximize its use and reduce the impact of risks arising from the accumulation of this waste in the environment [8]. Several studies report that valuable minerals containing the element iron (Fe) can be separated from other minerals in zircon mining waste by using differences in the magnetic properties of the minerals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation